2004
DOI: 10.1007/s00284-003-4143-0
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Azo Dyes with Enterobacter agglomerans Immobilized in Different Supports by Using Fluidized Bed Bioreactor

Abstract: Immobilized cells of Enterobacter agglomerans, able to reduce azo dyes enzymatically, were used as a biocatalyst for the decolorization of synthetic medium containing the toxic azo dye methyl red (MR). This bacterial strain exhibits high ability to completely decolorize 100 mg/L of MR after only 6 h of incubation under aerobic conditions. Cells of E. agglomerans were immobilized in calcium alginate, polyacylamide, cooper beech, and vermiculite, and were used for the decolorization of MR from synthetic water by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…UAP-b5 was initially supported on SOMAP2, the decolorization rate of RB5 and BB41 solutions was lower than for bacteria growing in liquid medium. In contrast, 95% of a methyl red solution [23] was decolorized by supported P. agglomerans in 6 h.…”
Section: Decolorization Of Immobilized Dyesmentioning
confidence: 84%
See 2 more Smart Citations
“…UAP-b5 was initially supported on SOMAP2, the decolorization rate of RB5 and BB41 solutions was lower than for bacteria growing in liquid medium. In contrast, 95% of a methyl red solution [23] was decolorized by supported P. agglomerans in 6 h.…”
Section: Decolorization Of Immobilized Dyesmentioning
confidence: 84%
“…Similarly, Nigam et al [24] previously reported fungi-mediated decolorization of RB5 after 48 h and Mohanty [1] reported a reduction of 46% in the amine metabolite concentration after 48 h following a two-stage anaerobic-aerobic treatment using sludge. Following the results of Moutaouakkil et al [23], we assume that the anaerobic decolorization of the immobilized dye coincided with the growth of Klebsiella sp. UAP-b5.…”
Section: Decolorization Of Immobilized Dyesmentioning
confidence: 98%
See 1 more Smart Citation
“…18 genera with relative abundance > 1% in the four microbial communities were shown in Table 2. Enterobacter obviously dominated in all samples (relative abundance varied from 30.61 to 40.06%) which was capable of azo dye reduction [31] as well as electricity generation [32]. Desulfovibrio presented > 5% of relative abundance in all samples and was reported to be involved in electricity generation [33] and azo dye reduction [34].…”
Section: Potential Function Of Dominant Generamentioning
confidence: 97%
“…Certaines de ces bactéries, telles que Enterobacter agglomerans (MoUTAoUAkkIL et al, 2003;MoUTAoUAkkIL et al, 2004) D'autres sont capables d'utiliser les amines aromatiques formées comme sources uniques de carbone, aboutissant ainsi à une dégradation complète ou « minéralisation » des colorants azoïques. Ces bactéries dégradent les molécules colorantes par la succession de deux étapes enzymatiques : une azoréduction, non sensible à l'oxygène, suivie d'une métabolisation à oxygène dépendant (BLüMEL et al, 1998;WoNG et yUEN, 1998).…”
Section: Décoloration Par Les Bactériesunclassified